Tax odysey-tax evasion wchich ends with penalty? - Woźniak, Krzysztof, Raul (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
The doctrine states that tax evasion is a legal action, albeit not tolerated by the state. The legality of tax evasion is of private law character, under the Tax Law tax evasion results in deprivation of the illegal tax benefit. Self-assessment which is non-compliant with the factual proceeding of the taxed actions, is penalized by the Penal Fiscal Law as tax fraud. The objective of this paper is to indicate the limits beyond which legal actions, procedurally compliant with the Tax Law, become criminal. The doubts raised by the taxpayer through acting contrarily to the objective and the spirit of the Tax Law may bring not only financial consequences but also criminal penalty.